1994
DOI: 10.1093/bja/72.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia: comparison with EEG indices during isoflurane anaesthesia at 0.65 and 1.2 MAC

Abstract: Respiratory sinus arrhythmia (RSA) is a cyclical variation in heart rate during breathing, where the heart rate increases during inspiration and decreases during expiration. RSA and the electroencephalogram (EEG) were monitored in 10 patients undergoing elective surgery with isoflurane and nitrous oxide in oxygen anaesthesia after induction with propofol. All patients were subject to controlled ventilation and recovery from competitive neuromuscular block was facilitated by neostigmine and glycopyrronium (seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In individual patients, increase in the RE-SE difference was seen already some minutes before the approaching emergence could be anticipated from SE or BIS. This observation may be related to the findings of early recovery of other brainstem-controlled phenomena, such as the respiratory sinus arrhythmia (15), suggesting that the anesthetic drug effect may cease at the brainstem level Muscles of the upper part of the face are innervated by the 7th cranial nerve, with their function only partly under voluntary control. Electrical activity of the upper facial muscles is of rather high frequency, mostly above 32 Hz (17).…”
Section: Discussionmentioning
confidence: 84%
“…In individual patients, increase in the RE-SE difference was seen already some minutes before the approaching emergence could be anticipated from SE or BIS. This observation may be related to the findings of early recovery of other brainstem-controlled phenomena, such as the respiratory sinus arrhythmia (15), suggesting that the anesthetic drug effect may cease at the brainstem level Muscles of the upper part of the face are innervated by the 7th cranial nerve, with their function only partly under voluntary control. Electrical activity of the upper facial muscles is of rather high frequency, mostly above 32 Hz (17).…”
Section: Discussionmentioning
confidence: 84%
“…Anaesthesia, both type and depth can influence RSA [21,22]. However, the depth of anaesthesia was a controlled variable in our experiment as we employed a continuous infusion of propofol/ketamine with a cross-over design, thereby minimizing time effects.…”
Section: Discussionmentioning
confidence: 99%
“…Pomfrett et al . [13, 24] reported that respiratory sinus arrhythmia responds promptly to different levels of anaesthesia and recovery, in addition to the degree of surgical stimulation, while the EEG indices responded with some delay; these findings suggest that respiratory sinus arrhythmia may be used as a tool to gauge the depth of anaesthesia according to the surgical needs, and may be a better indicator of MAC than the EEG [25].…”
Section: Discussionmentioning
confidence: 99%